Thermo-mechanical properties of cubic lanthanide oxides - Miran, H.; Altarawneh, M.; Widjaja, H.; Jaf, Z.; Mahbubur Rahman, M.; Veder, Jean-Pierre; Dlugogorski, B.; Jiang, Z. (Elsevier S.A., 2018)
This contribution investigates the effect of the addition of the Hubbard U parameter on the electronic structural and mechanical properties of cubic (C-type) lanthanide sesquioxides (Ln2O3). Calculated Bader's charges confirm the ionic character of LnO bonds in the C-type Ln2O3. Estimated structural parameters (i.e., lattice constants) coincide with analogous experimental values. The calculated band gaps energies at the Ueff of 5 eV for these compounds exhibit a non-metallic character and Ueff of 6.5 eV reproduces the analogous experimental band gap of cerium sesquioxide Ce2O3. We have thoroughly investigated the effect of the O/Ce ratios and the effect of hafnium (Hf) and zirconium (Zr) dopants on the reduction energies of CeOx configurations. Our analysis for the reduction energy of CeO2, over a wide range of temperatures displays that, shuffling between the two +4 and +3 oxidation states of Ce exhibit a temperature-independent behaviour. Higher O/Ce ratios necessitate lower reduction energies. Our results on CeHfZrO alloys are in reasonable agreements with analogous fitted values pertinent to lowering reduction energies and shrinkage in lattice parameters when contrasted with pure CeO2. Structural analysis reveals that Hf and Zr atoms in the solid solution are shifted towards the nearest vacancies upon reduction. It is hoped that values provided herein to shed an atomic-base insight into the reduction/oxidation thermodynamics of increasingly deployed catalysts for environmental applications.